2016
DOI: 10.1139/cjpp-2016-0197
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of kolaviron and gallic acid against cobalt-chloride-induced cardiorenal dysfunction via suppression of oxidative stress and activation of the ERK signaling pathway

Abstract: Cobalt (Co) toxicity is a potential public health problem due to recent renewed use of Co in orthopedic implants, dietary supplements and blood doping in athletes and horses. We investigated the protective roles of Kolaviron, KV (a bi-flavonoid of Garcinia kola) and Gallic acid (GA) on cobalt chloride (CoCl 2 ) -induced cardio-renal damage in rats. CoCl 2 caused significant increases (p<0.05) in serum creatine kinase-myocardial band (CK-MB), lactate dehydrogenase (LDH), aspartate transaminase (AST), xanthine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…From our laboratory, we have described the negative impact of CoCl 2 on blood pressure parameters and the use of synthetic and natural antioxidants for the amelioration of CoCl 2. 49,50 Oxidative stress has been suggested as a pathogenic factor and therapeutic target in early stages of essential hypertension, with the SBP and DBP correlating positively with reduction in the total antioxidant capacity of plasma in hypertensive subjects. 51 Hence, enzymatic and nonenzymatic antioxidants can mitigate the development of oxidative stress and associated dysregulation of biological systems through several mechanistic processes including a direct scavenging activity on ROS/ reactive nitrogen species (RNS) or inhibition of ROS/ RNS formation.…”
Section: Discussionmentioning
confidence: 99%
“…From our laboratory, we have described the negative impact of CoCl 2 on blood pressure parameters and the use of synthetic and natural antioxidants for the amelioration of CoCl 2. 49,50 Oxidative stress has been suggested as a pathogenic factor and therapeutic target in early stages of essential hypertension, with the SBP and DBP correlating positively with reduction in the total antioxidant capacity of plasma in hypertensive subjects. 51 Hence, enzymatic and nonenzymatic antioxidants can mitigate the development of oxidative stress and associated dysregulation of biological systems through several mechanistic processes including a direct scavenging activity on ROS/ reactive nitrogen species (RNS) or inhibition of ROS/ RNS formation.…”
Section: Discussionmentioning
confidence: 99%
“…CoCl 2 was intraperitoneally injected 24 h prior to cardiac ischemia at a dose of 30 mg/kg (Akinrinde et al, 2016). Blood glucose levels were controlled between 3.9 and 5.8 mmol/L with the following regimen: 3 U/d of intermediate-acting insulin was administered 48 h before cardiac ischemia, and 2U of short-acting insulin was administered 1 h before the experiment (Drenger et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, treatment with gallic acid mitigated diazinon induced cardiorenal toxicity by reducing cardiac and renal NO, besides alleviating oxidative stress and improving the hematological parameters of rats (Ajibade et al, 2016). Akinrinde et al (2016) reported the protective effects of gallic acid against cobalt-chloride-induced cardiorenal dysfunction via suppression of oxidative stress and activation of the ERK signalling pathway, besides downregulating plasma C-reactive protein (CRP) and the NO level. Also, Ryu et al (2016) showed that gallic acid limits isoproterenol-induced cardiac fibrosis and hypertrophy through modulation of Smad3 binding activity and JNK2 signalling in both in vitro and in vivo settings.…”
Section: Gallic Acidmentioning
confidence: 99%